Documentación de los procesos de restauración arquitectónica - Ros Sempere, Marcos (Cuadernos de Documentación Multimedia, 2009)
The article describes the theorems and an application model in the Information Science techniques in the architecture restoring. The phases are analyzed and a proposition of minimum requirements for the architecture restoring process is done. At last the author consider the need of achieving a normalization of the model.